Adenotonsilectomia e expansão rápida da maxila no tratamento da apnéia obstrutiva do sono infantil - Cunha, Thays Crosara Abrahão (2019)
Obstructive Sleep Apnea (OSA) affects about 2% of pre-school children and is associated with different comorbidities, some of which have implications in adult life. It is an underdiagnosed and under-treated disease due to the high cost and difficulty of access to polysomnography and adenotonsillectomy surgery. The objective of this study was to verify the effect of rapid maxillary expansion (RME) in the treatment of children with OSA. This thesis is composed of an introduction and three chapters. Chapter 1: Comparison of the effects of adenotonsillectomy and rapid maxillary expansion in obstructive sleep apnea in children - a controlled randomized prospective study. We evaluated the effect of RME and adenotonsillectomy (ADT) on the subjective and objective parameters of sleep, Doppler echocardiography, spirometry and quality of life of children with OSA. Children with AHI ≥ 2, tonsil hypertrophy and craniofacial changes were randomly selected in two groups: ADT and RME. The exams and questionnaires were applied before and after 4 months of the interventions. Our results demonstrate that both treatments significantly reduced AHI, but only one of the interventions failed to normalize all polysomnographic parameters. More studies are needed to determine predictors of success and establishment of sequencing for therapeutic protocol. The overlap of therapies and multiprofessional care is recommended. Chapter 2: Diagnostic Capacity of Salivary Biomarkers in Obstructive Sleep Apnea - Systematic Review of Literature. This systematic review adhered to the PRISMA check list and was registered at PROSPERO under the number: CRD42016037278. The α-amylase and the AHSG protein were identified as possible salivary biomarkers for diagnosis of OSA, however the diversity among the samples studied, the small sample size, the difference in the definition of OSA classification, as well !11 as the absence of studies that validate these findings, hinder their design of use for clinical practice. The development and validation of economically acceptable salivary biomarkers can improve diagnosis and accelerate access to treatment of suspected OSA patients. Chapter 3: Rapid Expansion of the Maxilla Suppresses Oval Patent Foramen in a Child with Obstructive Sleep Apnea - Clinical Case Report. Communication between the right and left sides of the heart is called the Oval Patent Foramen (OPF) and is considered a risk factor for diseases associated with embolism. A child with OSA and OPF underwent ERM and observed improvement in subjective facets and objectives of sleep, quality of life, tomographic parameters in addition to total suppression of FOP. We postulated that the area gain and the increase of the narrower Upper Airway region provided less resistance to the airflow passage, and as a consequence, an improvement in the pressures of the thoracic cavity favoring the closure of the OPF. These results suggest a relationship between OSA and the presence of FOP besides the possibility of reversion of the clinical picture through ERM.